Genetics of Interleukin 1 Receptor-Like 1 in Immune and Inflammatory Diseases - Akhabir, Loubna; Sandford, Andrew (Current Genomics, 2010)
Interleukin 1 receptor-like 1 (IL1RL1) is gaining in recognition due to its involvement in immune/inflammatory disorders. Well-designed animal studies have shown its critical role in experimental allergic inflammation and human in vitro studies have consistently demonstrated its up-regulation in several conditions such as asthma and rheumatoid arthritis. The ligand for IL1RL1 is IL33 which emerged as playing an important role in initiating eosinophilic inflammation and activating other immune cells resulting in an allergic phenotype. An IL1RL1 single nucleotide polymorphism (SNP) was among the most significant results of a genome-wide scan investigating eosinophil counts; in the same study, this SNP associated with asthma in 10 populations. The IL1RL1 gene resides in a region of high linkage disequilibrium containing interleukin 1 receptor genes as well as interleukin 18 receptor and accessory genes. This poses a challenge to researchers interested in deciphering genetic association signals in the region as all of the genes represent interesting candidates for asthma and allergic disease. The IL1RL1 gene and its resulting soluble and receptor proteins have emerged as key regulators of the inflammatory process implicated in a large variety of human pathologies We review the function and expression of the IL1RL1 gene. We also describe the role of IL1RL1 in asthma, allergy, cardiovascular disease, infections, liver disease and kidney disease.
Keywords: ERK2